Research on quality detection method for axis-hole interference fit based on laser ultrasound. (November 2021) - Zhou, Yang; Li, Hongchao; Wu, Genshang; Sun, Xinyao; Li, Dalei
Highlights: The evaluation platform of interference fit assembly quality based on laser ultrasound was built. The model that describes the relationship between the interference value and the guided wave power was established. The detection and location method for small cracks in interference fit assembly based on laser ultrasound was proposed. Abstract: The interference fit quality determines the equipment's service performance. In this work, interference fit assembly quality was evaluated using a laser ultrasonic method, including the assembly state of the interference fit. The power spectral density was used to calculate the power of the guided waves, and an interference assembly state evaluation method was proposed. Contact edge micro-cracks were identified by acquiring the full-field waveform propagation diagram, and these cracks were located by coupling the scanning area with the crack location. The center coordinate error for crack detection, which can basically determine the exact crack location, ranged between 0.09 mm and 0.15 mm. The length and width measurement errors ranged from 0.01 mm to 0.04 mm and 0.02 mm to 0.09 mm, respectively. The relationship curve between the guided wave power and interference was obtained experimentally. This method provides a new method for detection of the interference assembly structure state and the micro-cracks.